UPAYA INDONESIA MEMPERJUANGKAN KUOTA PENANGKAPAN TUNA DI KAWASAN SAMUDERA HINDIA DI FORUM INDIAN OCEAN TUNA COMMISSION (IOTC) TAHUN 2017 - Azzura, Nur; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research analyses Indonesia’s effort to advovate for tuna fishing quota in the Indian Ocean region at the IOTC forum in 2017. Tuna fishing in the Indian Ocean region has nearly reached the fishing limit, thus a regulation on fishing quota in the area is needed. The IOTC is a regional organization that has the authority to allocate fishing quotas to its member countries. As a permanent member of the IOTC and one of the largest coastal state of the Indian Ocean, Indonesia had the interest to secure its fishing quota in accordance to the length of the coastal that Indonesia has. This research uses qualitative research method where the data are collected through document analysis technique. In analyzing this topic, the author applies the economic diplomacy theory where actors pursue their countries’ economic interests through dialogue and negotiation in a multilateral forum or international organization such as IOTC. This research shows Indonesian government used the 2017 IOTC forum to pursue its interest in securing its tuna fishery. The Indonesian government persuaded other IOTC members to design new-approaches for tuna management that are fair, transparent, balance, and sustainable. Keywords: Tuna fishery, Indian Ocean, IOTC, RFMO, TCAC, fishing quota, Indonesia, economic diplomacy.